Based on the Beers Criteria 2019 Edition Over-the-Counter Drugs Risk Confirmation of Elderly Chinese. (25th August 2021) - Yang, Yongyu; Zhang, Lu; Huang, Yamin; Huang, Hangxing; Sun, Shusen; Xiao, Jian
Abstract : Objective . To explore OTC (over-the-counter drugs) in Chinese community pharmacies often causes ADE (adverse drug event) in elderly patients. Methods . Use the drugs in the Beers Criteria 2019 potentially inappropriate medication use (PIM) list as search terms. Search for drugs registered on the National Medical Products Administration of China website before December 2019 to determine the drugs containing PIM active ingredients and, then, search the Chinese OTC selection and conversion catalog database to determine it as OTC. Two databases are considered to be the same drug if they have the same drug composition. Results . The incidence of PIM in elderly patients in our community is relatively high, and the management of OTC may be related to risk factors. Statistics found that 71 OTC contained the Beers Criteria ingredients, including 65 chemicals and six Chinese patent medicines. Varieties of compound preparations accounted for 78.9% and cold medicines accounted for 47.9%. Conclusions . The high detection rate of the Beers Criteria in Chinese OTC suggests that medical practitioners in China, especially community pharmacists, should pay attention to the rational use of OTC in the elderly.